Tumour immune escape via P2X7 receptor signalling - Sainz, Ricardo M.; Rodriguez-Quintero, Jorge Humberto; Maldifassi, Maria Constanza; Stiles, Brendon M.; Wennerberg, Erik (Frontiers in Immunology, 2023)
While P2X7 receptor expression on tumour cells has been characterized as a promotor of cancer growth and metastasis, its expression by the host immune system is central for orchestration of both innate and adaptive immune responses against cancer. The role of P2X7R in anti-tumour immunity is complex and preclinical studies have described opposing roles of the P2X7R in regulating immune responses against tumours. Therefore, few P2X7R modulators have reached clinical testing in cancer patients. Here, we review the prognostic value of P2X7R in cancer, how P2X7R have been targeted to date in tumour models, and we discuss four aspects of how tumours skew immune responses to promote immune escape via the P2X7R; non-pore functional P2X7Rs, mono-ADP-ribosyltransferases, ectonucleotidases, and immunoregulatory cells. Lastly, we discuss alternative approaches to offset tumour immune escape via P2X7R to enhance immunotherapeutic strategies in cancer patients.